Research on the souces of efficiency and implementation of transport logistics clusters - Постан, Михаил Яковлевич; Столяров, Геннадий Петрович (Eastern-European Journal of Enterprise Technologies, 2015)
The paper analyzes the notions, principles of forming, the classification, and effective functioning of transport logistics clusters (ТLCs). The study reveals peculiarities of the European classification and organizational structures of the leading European TLCs. We have pointed out advantages and identified the sources of cluster formations efficiency. We have introduced the notion of potential efficiency sources for TLCs whose composition is rationalized for port clusters and suggested the methods for the efficiency estimation on expanding the cluster resource base. The article presents the results of a synergetic effect from a joint use of port transshipment complexes by sea port operators. The devised and presented TLC organizational structure includes a Center for cluster development, a Board, a Secretariat, and Committees that implement specific projects to improve the cluster efficiency and development. The Committee on the operational control of resources is provided with a technology of managing vessels processing at interchangeable berths as well as principles for the allocation of additional income from the reduction of the vessels parking time. Transport logistics companies participate in joint cluster projects based on the companies’ complete independence as well as on voluntary and mutually beneficial conditions. The research is relevant due to the lack of publications on organizational forms and managerial decisions in the implementation of potential TLCs efficiency sources. The commonly considered organizational structures represent unions that are not aimed at solving specific problems of TLCs development and efficiency. The research has determined that implementation of the suggested organizational and managerial decisions considerably increases the economic efficiency and competitiveness of TLCs. The developed proposals for coordination and cooperation of TLC companies and enterprises can be practically useful in developing appropriate regional organizational structures.